Quantity Take Off pada Perencanaan Gedung Apartemen Menggunakan BIM Revit - Yadi, Seplika; Yusuf, Effendi; Soebandono, Bagus (Jurnal TeKLA, 2023)
The volume of work and materials in construction is one of the important aspects that can affect the budget of a construction as well as the procurement of materials. Small mistakes and the lack of accuracy of an estimator and quantity surveyor can cause cost overruns in the budget of a construction so that a method is needed to minimize the human error. Building Information Modeling (BIM) is one method that can be used to accurately represent materials and construction volumes where modeling utilizes digital modeling to support the Virtual Design and Construction (VDC) process. Revit is a software that implements the BIM system. The advantages of Revit are that apart from having a variety of families and items to support 3D modelling, Revit can do material take-off up to a layer, making it possible to do quantity take off with materials that have many layers. Revit can also detect clash detection which can detect collisions between fields before construction begins, which is very helpful in the construction process.